Huge yolk sac tumor in an adolescent girl: a case report - Jain, Amrita J.; Daver, Rekha G.; Patil, Anjali M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Germ cell tumours form a minority of all malignancies of the ovary. The common age group affected by yolk sac tumours is 11 to 24 years. Here, we present a case of yolk sac tumour in a 13-year-old girl who came with complaints of abdominal pain, distension and acute febrile illness. Fertility sparing surgery (Unilateral salpingo-oophorectomy) was done while the contra lateral ovary and uterus was conserved followed by combination chemotherapy postoperatively. As pprognosis of yolk sac tumours is highly stage-dependent, an early diagnosis can result in a drastic difference in the final outcome of the treatment of this highly aggressive disease. Besides the rarity of the tumour, the importance of the fact, that a vigilant and informed clinician can make an early and timely diagnosis of this condition even in girls of such a young age and make a drastic difference in the final outcome of the treatment, compels us to present this case.